L’ebrea errante. Uso popolare della Megillat Ester a Roma dopo Shoah e Liberazione - Artico, Davide (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The paper main theme is Esther in Purim parodies. As a study case, the Jewishcommunity in Rome is taken into consideration. In spite of the relatively small numbersof Holocaust victims among the Italian Jews, the traumatic memories of persecution werewell present in the survivors’ awareness. In the early post-war years, they felt a pressingneed to pass on their knowledge of the Holocaust to the younger. Apart from academicpapers and literary works of import, a number of popular texts appeared. One exampleis a version of the Tale of Purim written around 1950. The narration carries on the Italiantradition of Aggadah-style literature, and its language makes it one of the latest documentsfeaturing idioms of the now forgotten Jewish-Roman dialect. In the tale, the Holocaust isreferred to by equaling Hitler to the persecutor of the Jews as of Megillath Esther. In thatfashion, Esther as a literary character wanders from the ancient religious discourse to theextra-literary actuality.